Trade, FDI, and the Organization of Firms - Helpman, Elhanan (Journal of Economic Literature, 2006)
New developments in the world economy have triggered research designed to better understand the changes in trade and investment patterns, and the reorganization of production across national borders. Although traditional trade theory has much to offer in explaining parts of this puzzle, other parts required new approaches. Particularly acute has been the need to model alternative forms of involvement of business firms in foreign activities because organizational change has been central in the transformation of the world economy. This paper reviews the literature that has emerged from these efforts. The theoretical refinements have focused on the individual firm, studying its choices in response to its own characteristics, the nature of the industry in which it operates, and the opportunities afforded by foreign trade and investment. Important among these choices are organizational features, such as sourcing strategies. But the theory has gone beyond the individual firm, studying the implications of firm behavior for the structure of industries. It provides new explanations for trade structure and patterns of foreign direct investment, both within and across industries, and has identified new sources of comparative advantage.